Effects of exogenous salicylic acid on the resistance response of wild soybean plants (Glycine soja) infected with Soybean mosaic virus. Issue 1 (2nd January 2020) - Zhang, Kai; Wang, Yu; Sun, Weiming; Han, Kemin; Yang, Min; Si, Zengzhi; Li, Guilan; Qiao, Yake
Abstract: Wild soybean ( Glycine soja ) is the ancestor of cultivated soybean ( Glycine max ). Soybean mosaic virus (SMV) is an important pathogen affecting soybean production worldwide. The effect of exogenous salicylic acid (SA) application on the disease resistance of wild soybean plants infected with SMV is still unclear. In this study, we determined the SA content; reactive oxygen species (ROS) content; lipid peroxidation level (malondialdehyde (MDA) content); enzymatic activities of peroxidase (POX), catalase (CAT), superoxide dismutase (SOD), and ascorbate peroxidase (APX); and expression of resistance-related genes in wild soybean plants inoculated with SMV after application of exogenous SA. Compared with control plants, H2 O2, O2 − and MDA were significantly increased and plant height, root length, leaf area and dry weight were significantly decreased after SMV inoculation. However, there were no significant differences between the control plants and those that had been treated with 1000 μmol·L −1 (1000×) SA 24 h before virus inoculation. The SA content; enzymatic activities of POX, CAT, SOD, and APX; and gene expression of GmPR-1, GmPR-10, GmNPR1, GmICS1, GmEDS1 and GmPR-2 in 1000 × SA-applied wild soybean plants were all significantly increased compared with those in the control plants. The results indicated that exogenous SA application on wild soybean plants before SMV infection could promote plant growth and increase the resistance of plants to the virus.